Eksplorasi Etnomatematika Batik Shibori pada Materi Geometri di SMA Plus Al-Falah Al-Makky - Nur Zahrotul Wakhidah; Annafi Awantagusnik (Kilau Publishing, 2025)
This study aims to explore ethnomathematical values within the practice of Shibori batik and connect them to geometric concepts in mathematics learning. A qualitative approach with ethnographic methods was employed. Data were collected through participatory observation, semi-structured interviews, and documentation at SMA Plus Al-Falah Al-Makky. The results reveal that the Shibori batik process contains geometric elements such as plane figures, reflective symmetry, rotational symmetry, and geometric transformations. Students were able to understand these concepts contextually through hands-on experience in batik-making. In addition to enhancing their understanding of geometry, this activity also fostered appreciation for local culture. These findings support the importance of culture-based mathematics instruction as a meaningful contextual learning approach. This study also opens opportunities for further research to explore other forms of local cultural practices that contain mathematical elements and have the potential to be used as contextual learning media. The development of ethnomathematics-based instructional models at various educational levels, as well as evaluating their effectiveness in improving students’ learning outcomes, becomes an important recommendation for future studies.